2021
DOI: 10.1007/s10439-021-02726-x
|View full text |Cite
|
Sign up to set email alerts
|

Soft Liver Phantom with a Hollow Biliary System

Abstract: Hepatobiliary interventions are regarded as difficult minimally-invasive procedures that require experience and skills of physicians. To facilitate the surgical training, we develop a soft, high-fidelity and durable liver phantom with detailed morphology. The phantom is anatomically accurate and feasible for the multi-modality medical imaging, including computer tomography (CT), ultrasound, and endoscopy. The CT results show that the phantom resembles the detailed anatomy of real livers including the biliary d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 29 publications
(40 reference statements)
0
10
0
Order By: Relevance
“…During transhepatic surgery, needle localization is the most critical parameter to be monitored under real-time Ultrasound (US) imaging guidance since it directly relates to the surgical outcome and patient safety. To give quantitative information with high temporal and spatial resolution during the needle insertion process, researchers presented a soft silicone liver phantom, characterized by an accurate biliary system and advanced sensorization [21]. The described phantom resembled a real liver also under endoscopy and computer tomography imaging.…”
Section: Digestive Systemmentioning
confidence: 99%
“…During transhepatic surgery, needle localization is the most critical parameter to be monitored under real-time Ultrasound (US) imaging guidance since it directly relates to the surgical outcome and patient safety. To give quantitative information with high temporal and spatial resolution during the needle insertion process, researchers presented a soft silicone liver phantom, characterized by an accurate biliary system and advanced sensorization [21]. The described phantom resembled a real liver also under endoscopy and computer tomography imaging.…”
Section: Digestive Systemmentioning
confidence: 99%
“…The simulation-based training involves the use of essential equipment and computer software to model a real scenario. Until now, most approaches in preoperative surgical planning focused on [ 4 , 5 ] live animal and ex vivo models, as well as virtual reality (VR) models. However, these procedures showed different disadvantages.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several studies have manufactured different realistic 3D models: kidney [ 4 ], brain [ 16 ], cardiac [ 17 , 18 ], neuroblastoma [ 19 ], liver [ 2 , 3 , 4 , 20 , 21 , 22 , 23 , 24 , 25 ], etc. However, most of the liver cases found in the literature had limitations, such as the accuracy of the 3D model and lack of quantitative quality validation in the production process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 Silicone-based phantoms are becoming more popular due to their structural stability, longer shelf life, and ease of handling. T 1 and T 2 relaxation times, US scattering parameters, and Hounsfield units (HU) of tissue-mimicking phantoms can be accurately manipulated by adding a proper concentration of other ingredients to the base recipe, such as water, 2 sugar, 28 cellulose, 33 glycerol,glass beads,sodium chloride, 34 and Gd-based MRI contrast agents. 30 In et al 2 suggested a mix of an ultraviolet (UV)-curable silicone with various concentrations of water and hydrophilic silicone (HS) for MRI/CT/US liver phantom fabrication.…”
Section: Introductionmentioning
confidence: 99%